A multimodal miniaturised soft robot for accessing remote areas by passive-flight and wall-climbing - Sriratanasak, Natthapol (2024)
Soft crawling robots have been developed to access confined and difficult-to-reach areas. Those robots have attracted the interest of the research community with various solutions to address design, crawling strategy, and modelling. However, their capabilities are limited by their own size and moving speed showing that crossing large obstacles and remote operation are still challenges. Human intervention is strongly required to deploy robots directly to the target area to avoid obstacles and reduce operating time. As such, they cannot inspect or navigate confined space and hazardous area where they cannot be deployed close enough. This limitation motivates authors to develop a multimodal soft robot that can be delivered to remote areas, where a human cannot reach, and perform navigation afterward.